2016
DOI: 10.1108/rpj-12-2014-0168
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and optimization of laser polishing of additive laser manufacturing surfaces

Abstract: Purpose Direct metal deposition (DMD) with laser is an additive manufacturing process enabling rapid manufacturing of complex metallic and thin parts. However, the final quality of DMD-manufactured surfaces is a real issue that would require a polishing operation. Polishing processes are usually based on abrasive or chemical techniques. These conventional processes are composed by many drawbacks such as accessibility of complex shapes, environmental impacts, high time consumption and cost, health risks for ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…For the argon trial (1.a), the increasing overlap results in an almost linearly decreased Sa. Moreover, the best results can be achieved for higher overlaps, which generally proves the findings that were presented by Rosa et al [24], Bhaduri et al [21], and Hafiz et al [23]. However, in the case of air, the lowest roughness is achieved for 85% Roughness analysis (Figure 10) reveals that an almost equal mean surface roughness (Sa) is achieved for OL = 50% for both the argon and air atmospheres (2.06 and 1.81 µ m, respectively).…”
Section: Influence Of Overlapsupporting
confidence: 89%
See 1 more Smart Citation
“…For the argon trial (1.a), the increasing overlap results in an almost linearly decreased Sa. Moreover, the best results can be achieved for higher overlaps, which generally proves the findings that were presented by Rosa et al [24], Bhaduri et al [21], and Hafiz et al [23]. However, in the case of air, the lowest roughness is achieved for 85% Roughness analysis (Figure 10) reveals that an almost equal mean surface roughness (Sa) is achieved for OL = 50% for both the argon and air atmospheres (2.06 and 1.81 µ m, respectively).…”
Section: Influence Of Overlapsupporting
confidence: 89%
“…Rosa et al reported that the overlap parameter has an impact on the surface integrity and surface roughness. Moreover, the authors highlighted that increasing overlap from 60% tends to create micro-cracks in the case of the CW-LP of 3D printed 316L steel parts [ 24 ]. Yung et al showed that the hatching distance can not only have an influence on roughness, but also on the wettability of the surface after LP [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy enables increase in interaction time between the laser and the surface, without increasing energy density for limit heat transfer for thin structures. The previous works on 316L material have shown that for 4 and 5 passes the surface evolution is limited [23]. For this reason, only 1 and 5 passes are applied to Ti6Al4V surfaces.…”
Section: Methodology Of Investigationmentioning
confidence: 99%
“…A few studies on laser polishing of titanium are proposed [16][17][18][19][20][21][22], but only one focus partially on laser polishing of LMD titanium surfaces [23]. In this study, laser polished LMD surfaces is investigated, but no multiscale analysis is effectuated.…”
Section: Introductionmentioning
confidence: 99%
“…Rosa et al examined the effect of laser polishing on stainless steel and Ti surfaces via laser metal deposition (LMD), and provided statistical models to determine the settings of operating parameters according to surface roughness specification. The results obtained a final surface roughness of 0.79-0.23 µm for an initial Sa of 21-1.8 µm [12]. Bhaduri et al reported laser polishing results in AM 316L stainless steel with the reduction of surface roughness from 3.8 µm to 0.2 µm [13].…”
Section: Introductionmentioning
confidence: 97%